Analisis Model Tripel Helix Dalam Pengembangan Ekonomi (Studi Pada IKM Kerajinan Perak Mojokerto) - Hariani, Danarti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Creative economy development aims to develop human resources so that they can compete with reliable quality. Rural areas, especially the Batankrajan Village area, are one of the areas in Mojokerto Regency that have the potential of creative human resources to improve the welfare of the local community. Batankrajan village and is the center of the silver industry which is quite potential as a competitive product and Mojokerto's leading commodity. The aims of this study were (1) to identify the conditions and needs for product development and market development of the craftsmen/performers of the silver craft business in Senta Batankrajan, Mojokerto, East Java, (2) to identify the problems faced by the craftsmen of silver crafts IKM in Mojokerto, East Java, especially in increasing competitiveness, (3) Analyzing the triple helix model in the development of the creative economy as a driving force for Mojokerto silver handicraft products to increase local innovative and creative products that are unique to the region and have high added value and are able to become regional icons. This research also identifies strengths, weaknesses, opportunities and threats that can be used as information to map the strengths and weaknesses of creative industry players so that strategies for developing the right Triple helix model can be formulated for business actors. This research produces an economic/creative industry model with a Triple helix approach that provides a role for stakeholders (government, universities and business actors) in advancing the creative industry in rural areas, especially the silver industry in the center of Batankrajan, Mojokerto. Several recommendations and the framework for developing the Triple Helix model in the development of the creative economy include: Institutional strengthening, through Joint Business Groups, in order to invest in product development and market penetration as well as facilitate the establishment of access to financial sources and market access, the creation and establishment of intensive communication between government, universities and creative industry players, as well as the establishment of community forums that involve the government, universities in the Mojokerto area and do not rule out universities outside Mojokerto as well as industry players that function as communication forums and as a means of coaching and training.